Otentisitas HadÃ®th MutawÃ¢tir dalam Teori Common Link G.H.A. Juynboll - Idri, idri (ISLAMICA: Jurnal Studi Keislaman, 2013)
Almost all Muslims agree that an authentic prophetic tradition (hadÃ®th) is that which comes directly from the Prophet. A tradition such as thisâlike the QurâÃ¢nâis reliable in terms of its chain of narration and message. Hence, it brings legal and moral implication for the Muslims to apply in their daily life. In the science of prophetic tradition, such tradition is called darÃ»rÃ®, literally means compulsory in the sense that it necessitates Muslims to comply. Different sort of view however, is being introduced by an orientalist named G.H.A. Juynboll. He comes up with an entirely different view concerning an authentic prophetic tradition both in terms of its category and definition. He reckons that there is no such thing as an authentic prophetic tradition. Every prophetic tradition is vague, and falls therefore under the category of being inauthentic. This paper is interested in dealing critically with this controversial view by giving particular attention to four main issues; the issue of definition, criteria, the number of narrators, and the rationale of a prophetic tradition to be deemed authentic.